Solidarities with the Non/Human, or, Posthumanism in Literature : Collected Essays on Critical Posthumanism, Volume 2 - Herbrechter, Stefan, (Critical Posthumanisms ;, 2025)
This volume collects essays written over the last decade by one of the founders and leading figures in the theoretical movement of critical posthumanism. The readings of literary texts gathered here, from Shakespeare, Keats, Camus, Vittorini, Kundera, Haushofer, Atwood, Eagleman, Crace and DeLillo, focus on 'posthumanist moments' in which questions of postanthropocentrism and the nonhuman become prominent, are negotiated and ultimately foreclosed. They show how a deconstructively-minded way of reading humanistically-motivated texts can help making these texts relevant for our so-called 'posthuman times'. In doing so, these critical posthumanist readings demonstrate that literature remains one of the privileged cultural institutions and practices from which solidarities both with and between the human and nonhuman can be formed and negotiated. See Less